Etika Berbusana Mahasiswa Stain Samarinda - Wijaya, Ida Suryani (FENOMENA, 2012)
Ethics is about behavior of human being, such as which one is right or wrong. The ethics is always affecting the human life. The ethics gives people orientation how he/she do manything every time every day. Islamic ethics consists of the way how someone interact each other; how someone should do or not to do, how to sit, how to walk, how to eat or drink, how to sleep, or how to get dressed. Al-Qur’an uses three terms to define about dressing, they are: libas, tsiyah, and sarahi. Dressing has a function as covering the body, as assessoris, as the way to do Islamic taqwa, and as an identiy. Dressing ethics of the female students of STAIN Samarinda has been regulated by the rector regulation No 19 of the year 2002 about relation and dressing ethics for the students of STAIN Samarinda.